Effect of body composition on survival benefit of hepatic arterial infusion chemotherapy for advanced hepatocellular carcinoma: A comparison with sorafenib therapy. - Issei Saeki (PLoS ONE, 2019)
Aim Sorafenib is used as a first-line treatment for advanced hepatocellular carcinoma (HCC). However, hepatic arterial infusion chemotherapy (HAIC) has also gained acceptance, but only in Japan. We explored the role of body composition as a factor affecting the survival benefit of HAIC compared to sorafenib for the treatment of advanced HCC. Methods We conducted a retrospective study using the clinical records of 133 patients with advanced HCC treated either with HAIC or sorafenib. Prior to treatment induction, skeletal muscle index and visceral fat area (VFA) were measured at the third lumbar vertebral and umbilical levels, respectively, using computed tomography. Muscle depletion and high-VFA (H-VFA) were defined using published cut-offs. We analyzed clinical parameters, including body composition as prognostic factors. Results In the HAIC group, multivariate analysis identified a positive response to HAIC (hazard ratio [HR], 0.438; p = 0.022), and conversion from HAIC to sorafenib (HR, 0.374; p = 0.008) as favorable prognostic factors for survival. In contrast, tumor number < 7 (HR, 0.475; p = 0.008), absence of extra-hepatic spread (HR, 0.511; p = 0.015), absence of muscle depletion (HR, 0.555; p = 0.044), and H-VFA (HR, 0.483; p = 0.015) were studied in the sorafenib group. Conclusions Body composition was identified as a prognostic factor for patient survival after treatment with sorafenib, but not for HAIC, and may be used as a biomarker when selecting between HAIC or sorafenib treatment of patients with advanced HCC. Additionally, conversion to sorafenib in patients receiving HAIC could improve survival regardless of response status.